'n Ondersoek na gronderosie in die Swartland - Germishuys, Hendrik Johannes (Cape Technikon, 2016)
Thesis (MTech (Civil Engineering))--Cape Technikon, 1992. === In the Western Cape, gully ("donga") erosion is characteristic of the Swartland area where the effects of the problem have reached spectacular dimensions. In 1942 the Social and Economic Planning Council commissioned an investigation into the distribution and prevention of gully erosion. This investigation was led by Professor W J Talbot of the University of Cape Town, with the collaboration of researchers from the University of Stellenbosch. This led to the "Swartland and Sandveld" publication in August 1945. Little progress has since been made. The gullies identified by Prof Talbot's team remain to this day. In most cases they have grown even longer and deeper. The present investigation aims to study a typical network in one catchment area and to propose measures for the reclamation or stabilization of gullies. Such measures must not only be effective but also economically justifiable. In reclaiming or stabilizing a donga, a key factor is the establishment of a foundation structure. Such a structure is essential for supporting semi-permanent structures and promoting the growth of grass and bushes. At present, however, no satisfactory methods are known for the design and construction of supporting walls In narrow, deep dongas, other than those methods that require a rock foundation. Furthermore, conventional methods would require a buttress of length 17 m for a retaining wall of height 4,4 m. The amount of concrete needed, would clearly be excessive. It is therefore one of the aims of this study to develop a retaining wall with a relatively short buttress. If finances permit, the retaining structure, will be built and the stabilization process carefully monitored for possible applications in the future.